Triggering the nanophase separation of albumin through multivalent binding to glycogen for drug delivery in 2D and 3D multicellular constructs. Issue 9 (18th February 2022) - Radziwon, Agata; Bhangu, Sukhvir K.; Fernandes, Soraia; Cortez-Jugo, Christina; De Rose, Robert; Dyett, Brendan; Wojnilowicz, Marcin; Laznickova, Petra; Fric, Jan; Forte, Giancarlo; Caruso, Frank; Cavalieri, Francesca
Abstract : Nanocomplexes of glycogen nanoparticles with serum albumin were formed by triggering the nanophase separation of albumin. The nanocomplexes enabled the delivery of chemotherapeutics in complex multicellular 3D tumour-like structures. Abstract : Engineered nanoparticles for the encapsulation of bioactive agents hold promise to improve disease diagnosis, prevention and therapy. To advance this field and enable clinical translation, the rational design of nanoparticles with controlled functionalities and a robust understanding of nanoparticle–cell interactions in the complex biological milieu are of paramount importance. Herein, a simple platform obtained through the nanocomplexation of glycogen nanoparticles and albumin is introduced for the delivery of chemotherapeutics in complex multicellular 2D and 3D systems. We found that the dendrimer-like structure of aminated glycogen nanoparticles is key to controlling the multivalent coordination and phase separation of albumin molecules to form stable glycogen–albumin nanocomplexes. The pH-responsive glycogen scaffold conferred the nanocomplexes the ability to undergo partial endosomal escape in tumour, stromal and immune cells while albumin enabled nanocomplexes to cross endothelial cells and carry therapeutic agents. Limited interactions of nanocomplexes with T cells, B cells and natural killer cells derived from human blood were observed. The nanocomplexes can accommodate chemotherapeutic drugs and release them in multicellular 2D and 3D constructs. The drugs loaded on the nanocomplexes retained their cytotoxic activity, which is comparable with the activity of the free drugs. Cancer cells were found to be more sensitive to the drugs in the presence of stromal and immune cells. Penetration and cytotoxicity of the drug-loaded nanocomplexes in tumour mimicking tissues were validated using a 3D multicellular-collagen construct in a perfusion bioreactor. The results highlight a simple and potentially scalable strategy for engineering nanocomplexes made entirely of biological macromolecules with potential use for drug delivery.